Hungary: Tax Competition Á La Hungary: Tax the Turnover and Relinquish the Income - Károlyi, Balázs (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter delves into the most recent issues of fiscal sovereignty regarding the Hungarian direct tax system. It highlights the actual and potential conflicts between domestic corporate tax rules (including not only corporate income tax provisions but also other types of special taxes) and primary and secondary EU law. In respect to clashes with primary EU law, this chapter explores the recent case law of the Court of Justice of the European Union in light of the fundamental freedoms and the EU Charter. Furthermore, regarding secondary EU law, this chapter considers the compatibility of domestic rules with the anti-avoidance directives as well as with the global minimum tax directive and argues that a proliferation of similar conflicts can be expected across the EU due to the peculiar nature and inherent mechanisms of the relevant directives.Keywords: tax sovereignty, fundamental freedoms, turnover taxes, global minimum tax, taxpayers’ rights, EU law, transposition, tax avoidance, tax competition, corporate taxation